The mediating role of organizational innovation on the relationship between knowledge management processes and organizational performancein the public sector - Naghavi, Mojtaba; Mohamed, Zainal Abidin; Sambasivan, Murali (Universiti Utara Malaysia, 2012)
The main objective of this study is to survey relationships among some of critical success factors of knowledge management (KM) include; KM processes (KMP), organizational innovation (INO), and organizational performance (PER). So in this research about the role INO as mediator will be investigated. The research proposes that KM in the public sector is still in its infancy and has a long way to go in the KM journey. However, the study has identified a certain number of factors that are essential to the success of the KM initiative and program in the public sector. The result of this investigation could have significant implications for KM programs in public sector organizations in Iran.